THE USE OF IRONY AND SATIRE IN THE CANTERBURY TALES - Eldorbek Erkin og’li Khamitov,; Turabayeva Ruhshona O’ktambekovna, (TADQIQOTLAR, 2026)
Abstract This  study  investigates  Geoffrey  Chaucer’s  use  of  irony  and  satire  in  The Canterbury Tales, focusing on how these literary tools critique the social, religious, and moral norms of 14th-century England. Chaucer’s irony frequently highlights the gap between  appearance  and  reality,  revealing  hypocrisy,  human  weaknesses,  and pretentious  behavior.  Through  satire,  he  examines  the  conduct  of  different  social groups—including the clergy, nobility, and peasants—showing the contrast between idealized values and actual practices. The paper analyzes key tales such as the Miller’s Tale, the Wife of Bath’s Tale, and  the  Summoner’s  Tale,  illustrating  how  humor,  exaggeration,  and  irony  are combined  to  expose  vices  like  greed, lust,  pride,  and  corruption.  Chaucer’s  use  of multiple narrative voices allows readers to experience a layered social commentary, making the work both entertaining and thought-provoking. Moreover, this research emphasizes the lasting impact of Chaucer’s techniques. His skillful blending of irony and satire not only portrays the complexities of medieval society but also offers a framework for understanding human behavior and societal critique in literature. Chaucer’s narrative strategies have influenced subsequent literary traditions, particularly in the use of humor as a method to reflect on social and moral issues.